Aryl hydrocarbon receptor/nuclear factor E2‐related factor 2 (AHR/NRF2) signalling: A novel therapeutic target for atopic dermatitis. Issue 4 (1st March 2022) - Hwang, Jonwei; Newton, Edita M.; Hsiao, Jennifer; Shi, Vivian Y.
Abstract: Aryl hydrocarbon receptor (AHR)/nuclear factor‐erythroid 2‐related factor 2 (NRF2) modulation is emerging as novel targets in the treatment of atopic dermatitis and other inflammatory skin disorders. Agonist activation of this pathway has downstream effects on epidermal barrier function, immunomodulation, oxidative stress reduction and cutaneous microbiome modulation. Tapinarof, a dual agonist of the AHR/NRF2 signalling pathway, has shown promise in phase 2 trials for atopic dermatitis. In this review, we summarize current knowledge of the AHR/NRF2 pathway and implications in skin disease process. We also review the therapeutic potential of current AHR agonists and propose future directions to address knowledge gaps.